2013
DOI: 10.21608/ejar.2013.167086
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Red Pigments Extracted From Red Beet (Beta Vulgaris, L.) and Its Potential Uses as Antioxidant and Natural Food Colorants

Abstract: Red pigments extracted from red beet (Beta vulgaris,L.) were identified for major constituents by using HPLC, these pigments were used as alternative natural red colorants in some processed foods, i.e. jelly and ice sherbets. Also, the effect of using red beet extract as natural antioxidant on corn oil was studied.The results showed that red beet had 380 mg betalain /100g on fresh weight. The major constituents' of red beet pigments were betalain and isobetalain by analyzing with HPLC. The best carriers for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…The results of the total betalain content from BEW and BED extracts were in accordance with [35], showing 3.80 mg/g on fresh weight. Through an HPLC analysis, it was found that the major constituents of red beet pigments were betalain and isobetalain.…”
Section: Beetroot Betalain Extraction By Dessupporting
confidence: 68%
“…The results of the total betalain content from BEW and BED extracts were in accordance with [35], showing 3.80 mg/g on fresh weight. Through an HPLC analysis, it was found that the major constituents of red beet pigments were betalain and isobetalain.…”
Section: Beetroot Betalain Extraction By Dessupporting
confidence: 68%
“…The use of betalains as natural antioxidants has also been studied in several foods. Attia et al (2013) studied the antioxidant effect of red beet roots in corn oil after seven days of storage at 60 °C, observing a decrease in the peroxide index with values similar to those obtained with BHT. Coria-Cayupán & Nazareno (2015) evaluated the protective effect of betalains from cactus pear fruits that were incorporated as natural pigments in dairy products (yogurt and cream), observing an inhibition of oxidative damage greater than 80% in yogurt and 50% in cream during the oxidation of the systems without the added pigments.…”
Section: Applications Of Betalains As An Additive In Foodmentioning
confidence: 81%
“…In the search for new sources of natural additives for use in food, numerous studies have evaluated the potential use of betalains as colorants, antioxidants, and antimicrobials. Attia et al (2013) evaluated the effect of incorporating red beet extract as a colorant in jelly and ice sherbets for its sensory properties, observing that the general acceptability of the products is dependent on the concentration of added betalains and on properties comparable to those of a synthetic red colorant. Betalains have also been incorporated as colorants for ice cream, and they improve the acceptability of the product and have good color stability for 180 days under storage at −20 °C ( Kumar et al, 2015 , Roriz et al, 2018 ).…”
Section: Applications Of Betalains As An Additive In Foodmentioning
confidence: 99%
“…Previous studies have demonstrated the great radical scavenging activity of betacyanins and betaxanthins. Attia et al (2013), Ravichandran et al (2013), and Mikolajczyk‐Bator & Czapski (2017) found that betalains had an antioxidant activity with DPPH (Attia et al, 2013; Mikolajczyk‐Bator & Czapski, 2017; Ravichandran et al, 2013).…”
Section: Resultsmentioning
confidence: 99%